Project management and project financed from the European Structural Funds - Košťálová, Jana; Tetřevová, Liběna (University of Pardubice, 2013)
This paper is dedicated to the problems of project management from the point of view of methodical rules for project financed from the European Structural Funds in the Czech Republic. It aims to identify problem-free, problem and collision areas of applicability of project management tools to projects co-financed from the European Structural Funds within the rules set from the side of grant providers in the Czech Republic. It discusses application of the project management tools in accordance with methodical rules within individual stages of a project life cycle, i.e., pre-project, project and post-project stages, and evaluates the system of methodical rules implemented in the Czech Republic for projects co-financed from the European Union sources in the context of project management.